Enhancing the teaching and learning of auditing: the case for descriptive feedback - Qhosola, Makeresemese Rosy (Faculty of Education, University of the Free State, 2017)
This paper demonstrates how the use of adequate descriptive feedback on assessment enhances the teaching, learning and academic performance of learners of auditing. Literature shows that this mode of feedback is transformative as it relies heavily on the particular, specific and localised learning styles of the individual learner. It also decolonises learning because learners are required to capitalise on their own meaningful indigenous strategies of learning. In order to generate data, the study used Critical Accounting Research as the theoretical framework, which emphasises the importance of delving deeper into socio-economic contexts to understand how good performance is created and sustained in the teaching and learning of auditing. Focus was on a selected school in the Free State where one grade 10 class, which used conventional feedback, was compared to another grade 10 class where descriptive feedback was used in the teaching of accounting. Tape recording of lessons in the respective classes was done. These were transcribed verbatim and critical discourses analysis was used to make sense of the data. The findings reveal that learners in the latter class were empowered to be critical and creative in their knowledge of auditing while the former continued to use rote and memorising approaches. Descriptive feedback created transformative spaces in the auditing classroom, made learners aware of multiple positions that can be assumed on any matter, ensured inclusivity of many forms of knowledges and showed that effective and continuous feedback was essential in discharging many misconceptions in auditing. The recommendation is that more classes of auditing should use descriptive feedback to transform and decolonise the learning of auditing.
Keywords: Descriptive feedback; Auditing; Critical accounting research; Participatory action research